Functional colour genes and signals of selection in colour‐polymorphic salamanders. Issue 7 (20th April 2020) - Burgon, James D.; Vieites, David R.; Jacobs, Arne; Weidt, Stefan K.; Gunter, Helen M.; Steinfartz, Sebastian; Burgess, Karl; Mable, Barbara K.; Elmer, Kathryn R.
Abstract: Coloration has been associated with multiple biologically relevant traits that drive adaptation and diversification in many taxa. However, despite the great diversity of colour patterns present in amphibians the underlying molecular basis is largely unknown. Here, we use insight from a highly colour‐variable lineage of the European fire salamander ( Salamandra salamandra bernardezi ) to identify functional associations with striking variation in colour morph and pattern. The three focal colour morphs—ancestral black‐yellow striped, fully yellow and fully brown—differed in pattern, visible coloration and cellular composition. From population genomic analyses of up to 4, 702 loci, we found no correlations of neutral population genetic structure with colour morph. However, we identified 21 loci with genotype–phenotype associations, several of which relate to known colour genes. Furthermore, we inferred response to selection at up to 142 loci between the colour morphs, again including several that relate to coloration genes. By transcriptomic analysis across all different combinations, we found 196 differentially expressed genes between yellow, brown and black skin, 63 of which are candidate genes involved in animal coloration. The concordance across different statistical approaches and 'omic data sets provide several lines of evidence for loci linked to functional differences between colour morphs, including TYR, CAMK1 and PMEL . We found little association between colour morph and the metabolomic profile of its toxic compounds from the skin secretions. Our research suggests that current ecological and evolutionary hypotheses for the origins and maintenance of these striking colour morphs may need to be revisited.